Dari Laporan Keuangan ke Nilai Pasar: Determinan Akuntansi Terhadap Nilai Perusahaan pada Industri Minyak dan Gas (Systematic Literature Review) - Adinda Putri Asyifa; Rina Tjandrakirana (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2026)
This study examines accounting determinants of firm value in the oil and gas industry using a Systematic Literature Review (SLR) approach. The study is motivated by inconsistent empirical findings and the limited capability of conventional financial indicators in explaining firm value in a capital-intensive and high-risk industry. The literature selection process follows the PRISMA 2020 guidelines, with Thematic Synthesis applied to analyze 13 selected articles published between 2020 and 2026. Based on the synthesis, this study concludes that profitability is the most consistent determinant in enhancing firm value. In contrast, variables such as capital structure, liquidity, firm size, and firm growth exhibit inconsistent relationships and tend to be context-dependent. These findings indicate that the influence of accounting variables is contingent and cannot be universally generalized. This study further highlights that a financial ratio-based approach alone is insufficient to comprehensively explain firm value in the oil and gas industry. External factors, including commodity price volatility and economic uncertainty, play a significant role in shaping firm value. Therefore, the development of more integrative analytical frameworks is necessary to improve the relevance of future research.